The effect of farmland abandonment on dung beetle diversity and function in the Nama-Karoo, Northern Cape, South Africa. - Steed, Adam John (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScConsEcol)--Stellenbosch University, 2020.